Effect of Formalin Vapour on The Kidney of Rabbits - Al-Hussany, Bahaa F. (The Iraqi Journal of Veterinary Medicine, 2004)
The purpose of this study was to evaluate the effect of formaldehyde on the kidney of rabbits. Treated animals were housed in closed room and exposed to formaldehyde fume using 10% formalin solution for a period of six months. Exposure was twenty-three hours for the whole period of the experiment, though one hour a day was left for ventilation. Control group was exposed to distilled water humidity. Histopathologically, there were glomerulonephritis, congestion, cellular infiltration in addition to other changes.